Comparative cytogenetics of the ground frogs Eupsophus emiliopugini Formas, 1989 and E. vertebralis Grandison, 1961 (Alsodidae) with comments on their inter-and intraspecific chromosome differentiation - Quercia, Camila A.; Suárez-Villota, Elkin Y.; Foresti, Fausto [UNESP]; Nuñez, José J. (Pensoft Publishers, 2020)
South American frogs of the genus Eupsophus Fitzinger, 1843 comprise 10 species. Two of them, Eupsophus vertebralis Grandison, 1961 and E. emiliopugini Formas, 1989 belong to the Eupsophus vertebralis group, exhibiting 2n = 28. Fundamental number differences between these species have been described using conventional chromosome staining of few specimens from only two localities. Here, classical techniques (Giemsa, C-banding, CMA3/DAPI banding, and Ag-NOR staining), and fluorescence in situ hybridization (FISH, with telomeric and 28S ribosomal probes), were applied on individuals of both species collected from 15 localities. We corroborate differences in fundamental numbers (FN) between E. vertebralis and E. emiliopugini through Giemsa staining and C-banding (FN = 54 and 56, respectively). No interstitial fluorescent signals, but clearly stained telomeric regions were detected by FISH using telomeric probe over spreads from both species. FISH with 28S rDNA probes and Ag-NOR staining confirmed the active nucleolus organizer regions signal on pair 5 for both species. Nevertheless, one E. emiliopugini individual from the Puyehue locality exhibited 28S ribosomal signals on pairs 4 and 5. Interestingly, only one chromosome of each pair showed Ag-NOR positive signals, showing a nucleolar dominance pattern. Chromosomal rearrangements, rRNA gene dosage control, mobile NORs elements, and/or species hybridization process could be involved in this interpopulation chromosomal variation.
Keywords: FISH; Karyotype variations; NOR polymorphism; Patagonian frogs; Ribosomal probe